2012
DOI: 10.1007/s11427-012-4422-8
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient uptake of ultrafine mesoporous silica nanoparticles with excellent biocompatibility by Liriodendron hybrid suspension cells

Abstract: The characteristics of the interactions co-cultures of ultrafine mesoporous silica nanoparticles (MSNs) and the Liriodendron hybrid suspension cells were systematically investigated using laser scanning confocal microscope (LSCM) and scanning electron microscopy (SEM). Using fluorescein isothiocyanate (FITC) labeling, the LSCM observations demonstrated that MSNs (size, 5-15 nm) with attached FITC molecules efficiently penetrated walled plant cells through endocytic pathways, but free FITC could not enter the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 28 publications
(36 reference statements)
2
6
0
Order By: Relevance
“…On the other hand, small non-functionalized MSNs (5-15 nm) in suspended walled cells were able to pass through the membrane via endocytosis. This demonstrates a bias of endocytosis towards small NP size (Xia et al, 2013). As a whole, these results show that positively charged NPs 5120 nm can be internalized by CFPE.…”
Section: Endocytosissupporting
confidence: 57%
“…On the other hand, small non-functionalized MSNs (5-15 nm) in suspended walled cells were able to pass through the membrane via endocytosis. This demonstrates a bias of endocytosis towards small NP size (Xia et al, 2013). As a whole, these results show that positively charged NPs 5120 nm can be internalized by CFPE.…”
Section: Endocytosissupporting
confidence: 57%
“…There have been significant successes in the use of mesoporous silica or other nanomaterials such as carbon nanotubes to deliver nucleic acids into plant cells. Besides nucleic acids, nanoparticles can also be functionalized with molecules such as fluorescent dyes for intracellular labeling in plants, active molecules for tracking and sensing purposes, and agrochemicals for crop health .…”
Section: Introductionmentioning
confidence: 99%
“…in Liriodendron hybrid suspension cells were able to pass through the cell wall and membrane via cellular endocytosis. (Xia et al, 2013) Endocytosis was also the main theory because SWNT's were found in "endocytosis like" vesicles and these results are similar to mammalian cell studies. (Shen, Zhang, Li, Bi, & Yao, 2010) Plant uptake in sucrose--coated (+) TiO2--NC with diameters of 2.8 ± 1.4 nm of Arabidopsis thaliana (thale cress) leaves was studied.…”
Section: Endocytosissupporting
confidence: 70%